EYE LESIONS IN SYPHILIS - D. V. Bokhonovich; O. K. Loseva; A. A. Ryabtseva; A. A. Kovrizhkina; V. M. Yudakova; N. V. Chernysheva (Российский офтальмологический журнал, 2018)
The paper is focused on diagnosing eye structure lesions in patients with syphilis. Two clinical cases are described: a case of syphilitic uveitis in early syphilis and optic nerve atrophy in late syphilis. The main purpose is to increase the awareness of ophthalmologists about specific eye diseases in syphilis and the need for early detection of such pathologies. For citation: Bokhonovich D.V., Loseva O.K., Ryabtseva A.A., Kovrizhkina A.A., Yudakova V.M., Chernysheva N.V. Eye lesions in syphilis. Russian ophthalmological journal. 2018; 11 (2): 46-53. doi: 10.21516/2072-0076-2018-11-2-46-53 (In Russian).